Dientamoeba fragilis in Ulcerative Colitis: Analysis of Clinical Findings and Biochemical Parameters - Ismail Taskiran; Erdogan Malatyali; Ibrahim Yildiz; Levent Durmus Guler; Evren Tileklioglu; Hatice Ertabaklar; Sema Ertug (Pathogens)
Although Dientamoeba fragilis is a common protozoan in humans, its pathogenicity and clinical significance in human diseases remain poorly understood. This study aimed to determine the frequency of D. fragilis in adult ulcerative colitis patients and to assess its relationship with clinical findings, disease characteristics, and biochemical parameters. Patient data were analysed in a prospective, single-centre, cross-sectional design. Faecal samples were consecutively collected from June to December 2024 and screened for D. fragilis positivity using polymerase chain reaction. Of the 110 patients, 33 (30%) were in the active stage of the disease, while 77 (70%) were in remission. The overall frequency of D. fragilis was 10.9% (n = 12), with all isolates classified as genotype 1 according to SSU rRNA sequence analysis. Other protozoa identified were Blastocystis sp. (n = 5, 4.5%), Entamoeba coli (n = 1, 0.9%), and Iodamoeba bütschlii (n = 1, 0.9%). Two patients were co-infected with D. fragilis and Blastocystis. No significant associations were found between D. fragilis positivity and the disease stage, gastrointestinal symptoms, treatment response, or biochemical findings. In conclusion, despite the relatively small sample size, these findings highlight a limited clinical role of D. fragilis in adult ulcerative colitis patients.